Academic procrastination among online students. Validation of a questionnaire - Martha Patricia Silva Payró (Universidad de Guadalajara, 2019)
The objective of this study was to validate a questionnaire based on the Academic Procrastination Scale (EPA), consisting of 16 items, to which six more were added related to internet interactions during the development of academic activities. The research was quantitative, descriptive, non-experimental and cross-sectional; using a questionnaire with a Likert-type scale it was applied to 746 students from all the undergraduate education programs who study online courses at a public university in Tabasco, Mexico. The statistical analysis revealed that in the context of the study, the bifactorial structure of EPA (academic self-regulation and procrastination) was confirmed, nine items of the EPA scale were discarded and five procrasting and internet items, which were designed for research, were validated.